2017
DOI: 10.1007/jhep12(2017)046
|View full text |Cite
|
Sign up to set email alerts
|

The photon content of the proton

Abstract: The photon PDF of the proton is needed for precision comparisons of LHC cross sections with theoretical predictions. In a recent paper, we showed how the photon PDF could be determined in terms of the electromagnetic proton structure functions F 2 and F L measured in electron-proton scattering experiments, and gave an explicit formula for the PDF including all terms up to next-to-leading order. In this paper we give details of the derivation. We obtain the photon PDF using the factorisation theorem and applyin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
284
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(291 citation statements)
references
References 68 publications
7
284
0
Order By: Relevance
“…Concerning the PDFs, we use the LUXqed plus PDF4LHC15 nnlo 100 set [57,58], which is in turn based on the PDF4LHC set [59][60][61][62]. This PDF set includes NLO QED effects in the DGLAP evolution and especially the most precise determination of the photon density.…”
Section: Input Parametersmentioning
confidence: 99%
“…Concerning the PDFs, we use the LUXqed plus PDF4LHC15 nnlo 100 set [57,58], which is in turn based on the PDF4LHC set [59][60][61][62]. This PDF set includes NLO QED effects in the DGLAP evolution and especially the most precise determination of the photon density.…”
Section: Input Parametersmentioning
confidence: 99%
“…Indeed, as discussed in the recent analysis of Ref. [20], it is possible to place quite precise constraints by using low-Q 2 inelastic structure function data. In this work, a dominantly coherent component was also included, and we have seen that the resultant photon PDF lies quite close to our prediction.…”
Section: Discussionmentioning
confidence: 99%
“…In general, as recently discussed in Ref. [20] this incoherent contribution may be constrained from experimental data on F 2 and F L ; however for our considerations it is sufficient to use a simplified model which gives an upper bound on such a contribution. Thus, following Refs.…”
Section: B the Input Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [10] studied the impact of the CMS measurements of W boson pair production at the LHC at 8 TeV on the NNPDF2.3qed, NNPDF3.0qed [11], CT14QEDinc [12], and LUXqed [13] photon PDFs, and found that the data strongly suggest that the NNPDF photon error band should be significantly reduced. Therefore, it is necessary to re-examine the physics effects induced by photon-initiated process.…”
Section: Introductionmentioning
confidence: 99%